The application of mirabilite in traditional Chinese medicine and its chemical constituents, processing methods, pharmacology, toxicology and clinical research - Tao, Lianbo; Fu, Jiaqing; Wang, Fangjie; Song, Yinglian; Li, Yi; Zhang, Jingwen; Wang, Zhang (Frontiers in Pharmacology, 2024)
This study reviews the use of mirabilite in traditional Chinese medicine and various preparations by describing its chemical composition, processing methods, pharmacology, toxicology, and clinical research progress. The main chemical component of mirabilite is sodium sulfate decahydrate (Na2SO4·10H2O), followed by small amounts of sodium chloride, magnesium sulfate, calcium sulfate, and other inorganic salts. This study systematically organizes the history of the medicinal use of mirabilite in China for more than 2,000 years. This mineral has been used by nine Chinese ethnic groups (Han, Dai, Kazakh, Manchu, Mongolian, Tujia, Wei, Yi, and Tibetan) in a large number of prescription preparations. The Pharmacopoeia of the People's Republic of China (2020 edition) records stated that mirabilite can be used for abdominal distension, abdominal pain, constipation, intestinal carbuncle, external treatment of breast carbuncle, hemorrhoids, and other diseases. The traditional processing methods of mirabilite in China include refining, boiling, sautéing, filtration after hot water blistering, and firing. Since the Ming Dynasty, processing by radish has become the mainstream prepared method of mirabilite. Mirabilite can anti-inflammatory detumescence, promote cell proliferation and wound healing, gastrointestinal motility. Mirabilite also has a variety of pharmacological effects, such as cholesterol-lowering effect,regulating intestinal flora, anti-muscle paralysis, anti-colon cancer, promoting water discharge, and analgesic. Only a few toxicological studies on mirabilite are available. External application of mirabilite can cause local skin to be flushed or itchy, and its oral administration is toxic to neuromuscular cells. The sulfur ions of its metabolites can also be toxic to the human body. At present, no pharmacokinetic study has been conducted on mirabilite as a single drug. This mineral has been widely used in the clinical treatment of inflammation, edema, healing of wound swelling and pain, digestive system diseases, infusion extravasation, hemorrhoids, skin diseases, milk accumulation, muscle paralysis, intestinal preparation before microscopic examination, and other diseases and symptoms. Mirabilite has good application prospects in traditional Chinese medicine and ethnomedicine. In-depth research on its processing methods, active ingredients, quality control, pharmacokinetics, pharmacological and toxicological mechanisms, and standardized clinical application is needed. This paper provides a reference for the application and research of mirabilite in the future.